A trainee’s right to a wage – the Estonian situation with comparative insights from Slovenia, the United States of America and Finland - Annika Rosin; Merle Erikson (Die Keure, 2022)
Although the initial aim of traineeships has been to ease young people’s transition from school to work, there is a tendency evolving in the European Union and in the United States of America (US) that trainees are used as cheap or free labour instead providing them with practical education. In this context the question of a trainees’ right to a wage is very important. This paper aims to answer the question of whether and under which conditions a trainee should be entitled to a wage in Estonia. It is concluded that a trainee fulfils the preconditions of receiving a wage and therefore, should receive one. However, we argue that in case education is provided during the traineeship, a trainee should not receive a wage in the same conditions as standard employees, but the obtainment of skills and knowledge could be regarded as a wage and/or the trainees could be paid subminimum wage. This would enable to avoid the exemption of trainees from the scope of labour law, guarantee them other labour rights and motivate employers to provide traineeships.